ESTIMATION OF THE PREDICTIVE EFFECT OF BODY MASS INDEX-PERCENTILE ON SKELETAL MATURATION IN A NIGERIAN POPULATION. - Osaronse Aghimien; Osasumwen Aghimien-Osaronse (Nigerian Dental Journal)
Objectives: To determine the predicting the effect of BMI-index percentile on the skeletal maturation of Nigerian children.